2001
DOI: 10.1002/1096-9861(20010226)431:1<59::aid-cne1055>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Kainate-activated cobalt uptake in the primary gustatory nucleus in goldfish: Visualization of the morphology and distribution of cells expressing AMPA/kainate receptors in the vagal lobe

Abstract: Gustatory afferent fibers of the vagus nerve that innervate taste buds of the oropharynx of the goldfish, Carassius auratus, project to the vagal lobe, which is a laminated gustatory nucleus in the dorsal medulla. As in the mammalian gustatory system, responses by second-order cells in the goldfish medulla are mediated by N-methyl-D-aspartate (NMDA) and non-NMDA ionotropic glutamate receptors. We utilized a cobalt uptake technique to label vagal lobe neurons that possess cobalt-permeable ionotropic glutamate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…To cobalt-label cells with Ca ϩϩ -permeable glutamate receptors, vagal lobe slices were prepared similar to previous studies (Smeraski et al, 2001;Sharp and Finger, 2002). In brief, goldfish were cold-anesthetized and the brain was removed quickly.…”
Section: Double Labeling With Immunohistochemistry and Cobalt Labelingmentioning
confidence: 99%
See 3 more Smart Citations
“…To cobalt-label cells with Ca ϩϩ -permeable glutamate receptors, vagal lobe slices were prepared similar to previous studies (Smeraski et al, 2001;Sharp and Finger, 2002). In brief, goldfish were cold-anesthetized and the brain was removed quickly.…”
Section: Double Labeling With Immunohistochemistry and Cobalt Labelingmentioning
confidence: 99%
“…In contrast, Korada and Schwartz (2000) show little correlation between CaBPs expression and the absence of GluR2 in the cochlear nucleus. The purpose of our study was to directly assess the degree of colocalization of Ca ϩϩ -permeable AMPA/kainate receptors and CaBPs in the primary gustatory nucleus in goldfish relying on direct visualization of the Ca ϩϩ -permeable neurons by kainatestimulated Co ϩϩ uptake as used previously by us (Smeraski et al, 2001) and other investigators (Pruss et al, 1991;Toomin and Millington, 1998;Yin et al, 1999;Van Den Bosch et al, 2000;Ogoshi and Weiss, 2003;Ogoshi et al, 2005).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results obtained in rat contrast with observations made in the goldfish. It was found that numerous neurons in the sensory layers of the vagal lobe (fish equivalent of the rostral gustatory portion of the mammalian NTS) were cobalt-labeled by kainate application and are therefore likely to possess calciumpermeable AMPA/kainate receptors (Smeraski et al, 2001;Ikenaga et al, 2006). Whether this apparent discrepancy originates from species differences or the investigated regions (mid-caudal general visceral part versus rostral gustatory part) remained to be determined.…”
Section: Ampa and Kainate Receptorsmentioning
confidence: 99%